Meta-analysis of plethysmography and rheography in the diagnosis of deep vein thrombosis. Issue 8 (20th July 2006) - Locker, T; Goodacre, S; Sampson, F; Webster, A; Sutton, A J
Abstract : Background: Plethysmography and rheography techniques have been widely studied as diagnostic tests for deep vein thrombosis (DVT). This study aimed to systematically review the accuracy of these tests for diagnosing clinically suspected DVT. Methods: The following databases were searched: Medline, EMBASE, CINAHL, Web of Science, Cochrane Database of Systematic Reviews, Cochrane Controlled Trials Register, Database of Reviews of Effectiveness, the ACP Journal Club (1966 to 2004), and citation lists of retrieved articles. Studies that compared plethysmography or rheography to a reference standard of ultrasound or contrast venography were selected. Standardised data were extracted and study quality determined against validated criteria. Data were analysed by random effects meta-analysis and meta-regression. Results: The meta-analysis included 78 studies, reporting 82 patient cohorts. Sensitivity and specificity (95% CI) were: 75% (73% to 77%) and 90% (89% to 91%) for impedance plethysmography, 83% (81% to 85%) and 81% (79% to 82%) for strain-gauge plethysmography, 85% (79% to 90%) and 91% (81% to 95%) for air plethysmography, 91% (87% to 94%) and 71% (66% to 75%) for light-reflex rheography, and 86% (83% to 89%) and 93% (91% to 95%) for phleborheography. Meta-regression was limited by poor reporting of studies. There was some evidence that diagnostic performance depended on the proportion of males in the cohort and reporting of study setting. Conclusions: Although plethysmography and rheography techniques add diagnostic value, they have inadequate diagnostic performance to act as a stand-alone test in DVT diagnosis. Evaluation of their role in combination with other tests, or standardised clinical assessment, is required.